The effects of iloprost on colonic anastomotic healing in rats under obstructive ileus conditions - Galanopoulos, Georgios; Raptis, Dimitrios; Pramateftakis, Manousos-Georgios; Mantzoros, Ioannis; Kanellos, Ioannis; Lazarides, Charalambos (Journal of Surgical Research, 2014)
The aim of this study was to investigate the effects of iloprost, on colonic anastomotic healing in rats, under obstructive ileus conditions.Eighty male Albino rats were randomized into four groups of 20 animals each. They underwent colonic resection followed by an inverted anastomosis. The rats of group 1 (control) and group 2 (ileus) received 3 mL of saline 0.9% intraperitoneally and those of group 3 (iloprost), and group 4 (ileus + iloprost) iloprost (2 ?g/kg of body weight), immediately postoperatively and daily until the day of sacrifice. Each group was further divided into two equal subgroups, depending on the day of sacrifice. The animals of subgroup "a" were sacrificed on the fourth postoperative day, whereas those of "b" on the eighth day. Macroscopic and histologic assessment was performed, whereas anastomotic bursting pressures and the tissue concentrations in hydroxyproline and collagenase I were evaluated.Means of bursting pressure, neoangiogenesis, fibroblast activity, and hydroxyproline concentration were significantly increased in group 4 compared with group 2. In addition, on the fourth postoperative day, the inflammatory cell infiltration and the collagenase I concentration were significantly decreased in group 4 compared with group 2. Moreover, on the eighth postoperative day, collagen deposition was significantly increased in group 4 compared with group 2.Iloprost after intraperitoneal administration reverses the negative effect of obstructive ileus. It promotes not only the angiogenic activity but also collagen formation, resulting in increased bursting pressures on the fourth and eighth postoperative days.
EVALuna2:15193